A comparison of sessional ratings of perceived exertion to cardiovascular indices of exercise intensity during competition in elite field hockey players - Perrotta, A. S.; Warburton, D. E. R. (Biomedical Human Kinetics, 2018)
Study aim: Recent evidence has revealed a reduction in the strength of correlation between ratings of perceived exertion and a heart rate (HR) derived training load in elite field hockey players during competition. These competitive periods involve sustained levels of cardiovascular performance coupled with considerable time performing above the anaerobic threshold. As such, the purpose of this investigation was to examine the magnitude of correlation between ratings of perceived exertion and time spent above threshold and two HR derived training loads. Material and methods: Seventeen (n = 17) international caliber female field hockey players competing as a national team were monitored over four matches during a seven-day competition period within the 2016 Olympic Cycle. Cardiovascular indices of exercise intensity were derived from HR dynamics and were quantified through estimating time spent above anaerobic threshold (LT2), the Edwards training load model (TLED) and the Polar Training Load (TLPOL). Sessional ratings of perceived exertion (sRPE) were recorded after each match. Results: 64 samples were recorded for analysis. HR derived (TLED & TL POL) and sRPE training loads remained comparable between matches. A large correlation (p = 0.01) was observed between sRPE and each heart rate derived training load (TLED & TLPOL). An unremarkable relationship (p = 0.06) was revealed between time spent above LT2 and sRPE. Conclusions: Our results demonstrate HR derived training loads (TLPOL & TLED) exhibit a stronger correlation with sRPE than time spent above LT2 in elite field hockey players during competition.